Intratympanic Injections of steroids For Treatment of sudden sensorineural hearing loss: Does the frequency of injections affect the outcome? - Usama taya (SVU - International Journal of Medical Sciences, 2022)
Background: Sudden sensory neural hearing loss (SSNHL) is an ENT emergency which is defined as a loss of hearing of 30 dB or more, over at least 3 successive frequencies, that develops within 3 days in most cases it is unilateral and the most age group to be affected are 40s and 50s in most cases the cause is not known and called idiopathic sensory neural hearing loss. pure tone audiometry is done to confirm the hearing loss, history, examination, MRI and blood tests to exclude serious underlying causes . Objective: to compare between the efficacy of four versus two intra tympanic injection of steroid for treatment of sudden idiopathic sensory neural hearing loss. Patients and Methods. During the time frame from February 2020 to January 2021 a thirty patients (15 males and 15 females) with ISSNHL who visited our otorhinolaryngology department, Qena university hospital. were merged with intra tympanic steroid injection for treatment of sudden sensory neural hearing loss. The ages rang was from 40 to 69. Results: According to our statistical analysis and data, hearing improvement after 4 intra tympanic injection is better than 2 injections with a p value is 0.000. Conclusion: Injection of 4 times intra tympanic injection of steroid appears to be more effective than two times of injection.